2019
DOI: 10.2139/ssrn.3332926
|View full text |Cite
|
Sign up to set email alerts
|

Governance, CO2 Emissions and Inclusive Human Development in Sub-Saharan Africa

Abstract: This study investigates the relevance of government quality in moderating the incidence of environmental degradation on inclusive human development in 44 sub-Saharan African countries for the period 2000-2012. Environmental degradation is measured with CO2 emissions and the governance dynamics include: political stability, voice and accountability, government effectiveness, regulation quality, the rule of law and corruption-control. The empirical evidence is based on the Generalised Method of Moments. Regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…Hence, we construct three sub‐indexes and a global governance quality index by applying the PCA method on six institutional variables. Following recent studies by Asongu and Nnanna (2019) and Asongu and Odhiambo (2019), the governance quality ( GOV ) is examined through an index of political governance, PGOV (political stability and absence of violence/terrorism [ PSTA ] and voice and accountability [ FRE ]), an index of institutional governance, IGOV (control of corruption [ COR ] and the rule of law [ LAW ]) and an index of economic governance, EGOV (government effectiveness [ GEF ] and regulatory quality [ REG ]). We also derive the global index of governance quality ( GOV ) from these six variables via the PCA method.…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…Hence, we construct three sub‐indexes and a global governance quality index by applying the PCA method on six institutional variables. Following recent studies by Asongu and Nnanna (2019) and Asongu and Odhiambo (2019), the governance quality ( GOV ) is examined through an index of political governance, PGOV (political stability and absence of violence/terrorism [ PSTA ] and voice and accountability [ FRE ]), an index of institutional governance, IGOV (control of corruption [ COR ] and the rule of law [ LAW ]) and an index of economic governance, EGOV (government effectiveness [ GEF ] and regulatory quality [ REG ]). We also derive the global index of governance quality ( GOV ) from these six variables via the PCA method.…”
Section: Methodsmentioning
confidence: 85%
“…Based on recent studies (Asongu & Odhiambo, 2019; Asongu & Nnanna, 2019; Kassi et al, 2020), we selected six variables of governance quality from the Worldwide Governance Indicators (WGI, 2018), namely, the political stability and absence of violence/terrorism ( PSTA ), voice and accountability ( FRE ), control of corruption ( COR ), the rule of law ( LAW ), government effectiveness ( GEF ), and the regulatory quality ( REG ). Following earlier studies and using the database from the World Development Indicators (WDI, 2018), we included several control variables, including consumer price index (Benczú et al, 2018; Gazdar & Cherif, 2015; Law & Singh, 2014), the official exchange rate (Kojid, Asid, Lily, Mulok, & Loganathan, 2012; Razzaque, Bidisha, & Khondker, 2017; Selimi & Selimi, 2017), and gross fixed capital formation (Kyophilavong et al, 2016; Musamali et al, 2014; Rahman & Velayutham, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a GMM estimation technique in 25 SSA countries over the period 1996 to 2010, Abid, (2016) found that democracy, government effectiveness, political stability, and control of corruption reduces CO2 emissions and on the other hand, rule of law and regulatory quality increases CO2 emissions. Asongu and Odhiambo (2020) investigated the importance of government quality in moderating the prevalence of environmental degradation on inclusive human development in 44 sub-Saharan African countries over the period 2000 to 2012. Based on a GMM they found that, Regulation quality, rule of law and corruption control modulates CO2 emissions to exert a net negative effect on inclusive human development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, it was also found that, the direct and negative effects of environmental degradation on health may be decreased by the indirect and positive effects through institutions quality and macroeconomic variables. Based on the research work of Asongu and Odhiambo (2020) on a panel of 44 sub-Saharan African countries from 2000 to 2012 regulation quality modulates carbon dioxide emissions to exercise a net negative effect on inclusive development. Institutional governance (corruption control and the rule of law) modulates CO2 emissions to also exert a net negative effect on inclusive human development.…”
Section: Literature Reviewmentioning
confidence: 99%